Rare disease centers for periodic paralysis: China versus the United States and United Kingdom. Issue 2 (February 2014) - Ke, Qing; Qi, Ming; Wu, Weiping; Luo, Benyan; Hanna, Michael; Herr, Barbara; Griggs, Robert C.; ,
ABSTRACT Introduction: We have developed a rare disease center in China. Methods: In this study we analyzed how patients with periodic paralysis accessed centers in China vs. in the USA and UK. Results: A total of 116 patients with periodic paralysis were evaluated in Beijing and Hangzhou (2003–2012). These patients traveled long distances for outpatient specialist care without an appointment or physician referral. In contrast, at the University of Rochester in the USA, >90% of patients were referred from physicians throughout the country by identifying physician expertise or by referrals from a patient advocacy group. In the UK, a single center, supported by the National Health Service, provides assessment/genetic testing for all UK patients. Conclusions: Rare disease centers in China require: (1) establishing a center for clinical characterization of the disease (e.g., periodic paralysis); (2) establishing a genetic diagnostic platform; (3) placing the center at a major city hospital; and (4) facilitating patient access through internet websites. Muscle Nerve49: 171–174, 2014